Шунт для вимірювання імпульсних струмів - Фальковський, М.І.; Божко, І.В. (Технічна електродинаміка, 2012)
The principles of design and construction of the shunt to measure pulse currents to 1 kA with fronts pulses over 1 μsec are described. The peculiarity of the shunt is a tubular bifilar design in which internal resistive tube replaced nichrome wires, located on the cylindrical surface. Small size shunt reached as a result of construction and technology of manufacturing it. Given the comparison of the characteristics of the shunt that obtained by using low-voltage ohmmeter, inductive sensor AC and oscillograms of voltage of the shunt. Considered the methodology, which is based on those oscilograms, which can also define parameter electrical circuit. It is shown that thermal resistance of the shunt is also provided.